Modeling a photovoltaic pumping system - Nedjem Eddine Benchouia; Yahia BELLARAGUEB; Belgacem MADI; Mounir BENADJA (Intternattiionall Semiinar iin Industtriiall Engiineeriing and Applliied Matthemattiics ((ISIEAM''2018), 2018)
The work presented in this paper concerns the modeling and simulation of a photovoltaic panel intended to drive a motor pump through a DC-AC converter (inverter). In our analysis, we designed a PV system where the PV generator is the isofoton module producing, under standard test conditions (CST), a peak power of 110W, an optimal current of 3.38 A and an optimal voltage of 43.2V. Indeed the characteristic I (V) of the generator depends on the solar illumination and the temperature. These climatic variations cause the fluctuation of the point of maximum power. The simulation results obtained under Matlab / Simulink show the performance of the dynamic behavior of photovoltaic systems. The comparison of the results obtained by simulation with experimental ones is essential.
Modélisation d’un système de pompage photovoltaïque